Improvement of analog-code converter - Mikhaylik, I.; Petrenko, K. (Geofizicheskiy Zhurnal, 2013)
A problem of applying the ship of single-channel programmable digital filter QF1D512 from the company Quickfilter Technologies for processing of digital data stream o f analog-digital code converter during seismic signal registration has been considered.